2013
DOI: 10.1117/12.2027029
|View full text |Cite
|
Sign up to set email alerts
|

A split- and delay-unit for the European XFEL

Abstract: For the European XFEL [1] an x-ray split-and delay-unit (SDU) is built covering photon energies from 5 keV up to 20 keV [2]. This SDU will enable time-resolved x-ray pump / x-ray probe experiments as well as sequential diffractive imaging [3] on a femtosecond to picosecond time scale. Further, direct measurements of the temporal coherence properties will be possible by making use of a linear autocorrelation. The set-up is based on geometric wavefront beam splitting, which has successfully been implemented at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Similarly, XFELs, like the Linac Coherent Light Source (LCLS) at SLAC National Accelerator Laboratory, have increased peak coherent X-ray brilliance by nearly 10 orders of magnitude ( Figure 1). The world's first hard X-ray FEL, the LCLS, began operations in 2009, and a recent summary of the first five years of operation highlights the numerous discoveries enabled by such sources that have fundamentally changed our understanding of materials behavior at the femtosecond and nanometer scale [9]. The success of the LCLS has spawned numerous other XFELs that are operation, or are soon to achieve first light in the near future, including SACLA at Spring-8 in Japan (operational in 2011), PAL-XFEL in South Korea (first light in 2016), the European XFEL in Germany (first light due in 2017), the Swiss FEL, and many other planned facilities.…”
Section: Executive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, XFELs, like the Linac Coherent Light Source (LCLS) at SLAC National Accelerator Laboratory, have increased peak coherent X-ray brilliance by nearly 10 orders of magnitude ( Figure 1). The world's first hard X-ray FEL, the LCLS, began operations in 2009, and a recent summary of the first five years of operation highlights the numerous discoveries enabled by such sources that have fundamentally changed our understanding of materials behavior at the femtosecond and nanometer scale [9]. The success of the LCLS has spawned numerous other XFELs that are operation, or are soon to achieve first light in the near future, including SACLA at Spring-8 in Japan (operational in 2011), PAL-XFEL in South Korea (first light in 2016), the European XFEL in Germany (first light due in 2017), the Swiss FEL, and many other planned facilities.…”
Section: Executive Summarymentioning
confidence: 99%
“…XPCS is used to study dynamics by comparing changes in coherent scattering from samples as a function of time [7], [8]. This method will be pushed to the limit of single X-ray pulse lengths by advances in X-ray split and delay technology [9]. In the following, we discuss two specific areas of opportunity for MaRIE studies of nanomaterials that were identified during this breakout session: nanomaterial growth and assembly.…”
Section: Opportunities For New Insight Into Structural Materials Usinmentioning
confidence: 99%
“…22 The first optical split-and-delay systems have been operated at visible to soft X-ray wavelengths. [23][24][25][26] Equivalent devices for hard X-rays have been discussed over many years. The first hard X-ray split-and-delay system, based on the perfect crystal optics and fixed scattering geometry, has been developed at DESY.…”
Section: Introductionmentioning
confidence: 99%
“…Fresnel's double mirror and Lloyd's mirror (Rus et al, 2001;Rocca et al, 1999), edge mirror splitting (Mitzner et al, 2008(Mitzner et al, , 2009Schlotter et al, 2010;Roling et al, 2011Roling et al, , 2012, half-splitted mirror (Moshammer et al, 2011)] and amplitude splitting [e.g. diffraction gratings (Goulielmakis et al, 2002) or semitransparent membranes].…”
Section: Introductionmentioning
confidence: 99%